Encouraging Women's Leadership and Empowerment in SME Businesses within SOEs as an Implementation of Core Moral Values - Susilowati E; Sadirsan ES (Yayasan Adra Karima Hubbi, 2024)
Background. Indonesian state-owned companies have the potential to increase Gross Domestic Product by USD 135 billion by 2025 if they can improve the status of gender equality in the world of work. Purpose. The Ministry of SOEs seeks to increase women's representation in the Board of Commissioners, Management Board and one level below the Management Council, with a target of 15% in 2021 and 25% in 2023. Method. The methodused by researchers in this study is descriptive analysis and Analytic Hierarchy Process (AHP). Results. The results obtained in this study are the leadership of women MSME owners who receive higher BUMN support than those who do not receive. While the novelty of this study is the leadership and empowerment of women in MSMEs within State-Owned Enterprises (MSMEs) Conclusion. There has also been an increased focus on the representation of young people within the Board of Directors, and below levels, from state-owned enterprises to 5% in 2021 and 10% in 2023.